Virus Elimination from Ornamental Plants Using in vitro Culture Techniques - Milosevic, Snezana Milutin (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Viruses are responsible for numerous epidemics in different crops in all parts of the world. As a consequence of their presence great economic losses are being incurred. In addition to the development of sensitive techniques for detection, identification and characterization of viruses, substantial attention has also been paid to biotechnological methods for their elimination from plants. In this review article, the following biotechnological in vitro culture techniques for virus elimination from ornamental plants are presented: meristem culture, thermotherapy, chemotherapy, cryotherapy or a combination of these methods. The plant species, as well as the type of virus determine the choice of a most suitable method. The state of the art in investigation of virus elimination from Impatiens sp. in Serbia is summarized.